Barthel index score in stroke patients increases after undergoing medical rehabilitation - Ganing, Sirly Nabireta Maharani; Subadi, Imam; Sugianto, Paulus (Folia Medica Indonesiana, 2016)
Stroke is the leading cause of death among Indonesian people over the age of five years, comprising 15.4% of all deaths, with a mortality rate of 99/100 000, and the number of disability is 685/100 000. Medical rehabilitation has an effect in improving functional status of patients with stroke, especially if it is done intensively in the first 6 months after stroke attack. Measurement of functional status is commonly used in clinic, including in Dr. Soetomo Hospital. However, no study had been conducted in measuring functional status using Barthel Index in Surabaya. Therefore, this study identified the difference of the functional status of stroke patients before and after undergoing medical rehabilitation. The study used an experimental method with pre and post design with total sampling. The samples were 47 stroke patients in Dr. Soetomo Hospital, Surabaya. Data were obtained from March - April 2014 using Barthel Index. Data analysis used Wilcoxon Sign Rank test, including the distribution of each variable, which showed signification value of <0.05. This study concluded that Barthel Index score increases after undergoing medical rehabilitation.